Status Fulfillment through Social Networks: Impact of Hierarchies on Social Differentiation and Well-being - Sipos, Dario (Technium Social Sciences Journal, 2024)
This study examines the multifaceted impacts of hierarchical systems and social networking on social differentiation, network formation, and individual well-being. Employing a comprehensive literature review and meta-analysis, it explores the dynamics of power and status within organizations, the influence of social resources on socioeconomic status, and the role of social networking sites in shaping social capital and psychological health. The research investigates how hierarchical structures within organizations and informal social settings contribute to social differentiation, examining the effects of power, status, and social resources on individual and group dynamics. Additionally, it assesses the impact of social networking sites on social well-being, career development, and psychological health, considering both the positive and negative consequences of online social interactions. The study reveals that while hierarchical systems and social networking can foster social capital, professional growth, and enhanced well-being, they also pose risks of social inequality, psychological distress, and exacerbated mental health issues. The findings underscore the complexity of social relations in the digital age, offering insights for developing more inclusive social structures and healthier digital interaction spaces. This research contributes to a deeper understanding of the interplay between social hierarchies, networking, and well-being, providing valuable implications for organizational leaders, policymakers, and individuals navigating social differentiation and digital socialization.